Pengembangan Pendidikan Vokasional Agribisnis dalam Rangka Peningkatan Kapasitas Produksi di Komunitas Kelompok Tani di Karang Rejo - Bambang Irawan; Ade Rahmad Kurniawan; Vina Oktaria; Anggi Pratama; Sugiono (Wisanggeni: Jurnal Pengabdian Masyarakat, 2023)
Abstract This community service program was conducted in Karang Rejo Village, Jati Agung District, South Lampung Regency. The primary objective was to enhance community knowledge and skills in hydroponic farming through the Asset-Based Community Development (ABCD) approach. The program focused on vocational agribusiness training based on local potential, particularly the introduction and hands-on practice of simple hydroponic techniques that can be applied at the household level. The results showed that participants were able to understand and implement basic hydroponic methods such as seed germination, nutrient mixing, and the use of recycled materials as growing media. In addition to improving technical skills, this program also encouraged food self-sufficiency, optimized the use of limited land, and reduced household consumption costs. It is expected that this activity will serve as a replicable community-based empowerment model for sustainable development.